The role of dimensions of social capital and sports participation in the social vitality of participants in public sports in Guilan - Parisa Saneie; Fatemeh Molaeifard Pileh Rood; Kazem Mehri (Social Determinants of Health)
Background: Social vitality, as one of the important indicators of quality of life, plays a key role in improving public welfare and social dynamics. Social capital and sports participation were among the most important variables affecting social vitality. The aim of this study was identifying and analyzing the importance of social capital and sports participation on the social vitality of participants in public sports.